دور التركيز على احتياجات العاملين في تحسين أداء العاملين في البنوك- دراسة تطبيقية في البنوك العاملة بولاية سكيكدة- - طويل, ياسمينة (جامعة الوادي University of Eloued, 2019)
This study aims to identify the reality of the focus on the needs of workers and its role in improving their performance in the Algerian banks, and was selected national and foreign banks operating in the province of Skikda (BADR, BDL, BNA, BEA, CNEP, CPA PARIBAS ,, ABC, AGB, TRUST Al Baraka Bank (Societe Generale), to conduct the application side of the study, a questionnaire list was used containing (40) phrases, distributed to a sample of (176) workers, and retrieved (135) questionnaires valid for analysisAfter the analysis using the Spss program, the results showed that there is a moderate degree of application by the banks under study to the dimensions of the workers' needs, which is (training, participation, motivation). The study also made several suggestions to Algerian banks in general and banks operating in the province of skikda in particular.
The role of the focus on employee needs in improving the performance of bank employees -An Applied Study in Banks Operating in Skikda
مقال
Keywords: البنوك ، التدريب، المشاركة، التحفيز، أداء العاملين.